Commensal small mammal trapping data in Southern Senegal, 2012–2015: where invasive species meet native ones. Issue 10 (26th August 2021) - Granjon, Laurent; Fossati‐Gaschignard, Odile; Artige, Emmanuelle; Bâ, Khalilou; Brouat, Carine; Dalecky, Ambroise; Diagne, Christophe; Diallo, Mamoudou; Gauthier, Philippe; Handschumacher, Pascal; Kane, Mamadou; Husse, Lætitia; et al.
Abstract: Describing patterns and testing hypotheses on processes driving biological invasions represent major issues in ecology. Addressing these questions requires building adequate data sets, i.e., covering areas and spanning periods adapted to the invasion processes studied. Rodents include major invasive species, among which the black rat Rattus rattus and the domestic mouse Mus musculus have nearly colonized the entire world, from their native Asian range. To do so, they have benefitted from their ability to cope with human‐modified environments and to live in the immediate vicinity of Man, who served as a vector of their dispersal between regions and continents. In Senegal, both R . rattus and M . musculus, initially introduced by early West European colonizers some centuries ago, are currently expanding thanks to road traffic and infrastructure development and rampant urbanization that concerns even remote regions of the country. As part of projects aimed at studying (1) the role of invasive black rat populations in the emergence of zoonotic diseases in southeastern Senegal, and (2) the evolutionary consequences of parasites in R . rattus and M . musculus invasions in Senegal, we conducted a series of field campaigns throughout the southern half of the country, between May 2012 and September 2015. The objectives were to catch commensal small mammals using standard trapping procedures, identify them using morphological or molecular tools, and take samples from them upon autopsy, to look for zoonotic parasites and pathogens. Along with data on individual specimens, information on microhabitats was gathered at each trap position. This resulted in the constitution of a data set of more than 13, 000 trapnights, which allowed the capture of more than 3, 100 small mammals, all characterized by a series of associated biological, geographical, and environmental data. The small mammals concerned are mainly rodents (10 species), shrews, and hedgehogs. The two invasive rodent species were the most numerous, exceeding in numbers all the other species pooled. This data set makes it possible to study coarse to fine‐scaled distribution of species of this commensal community in southern Senegal, as well as the possible determinants of this distribution in terms of habitat preferences and/or interspecific interactions. This data set can be freely used for non‐commercial purposes and is licensed under a Creative Commons Attribution 4.0 International License.